Diagnostic performance of choline PET for detection of hyperfunctioning parathyroid glands in hyperparathyroidism: a systematic review and meta-analysis - Treglia, Giorgio; Piccardo, Arnoldo; Imperiale, Alessio; Strobel, Klaus; Kaufmann, Philipp A.; Prior, John O.; Giovanella, Luca (European journal of nuclear medicine and molecular imaging, 2019)
Purpose Hyperparathyroidism (HPT) is a common endocrine disorder caused by hyperfunctioning parathyroid glands (HP). The correct detection and localization of HP is challenging but crucial, as it may guide surgical treatment, particularly in patients with primary HPT. There is a growing body of data regarding the role of radiolabelled choline positron emission tomography (PET) in this setting. Therefore, we performed a systematic review and meta-analysis of the diagnostic performance of this method in detecting HP in patients with HPT. Methods This systematic review and meta-analysis was carried out according to PRISMA guidelines. A comprehensive computer literature search of PubMed/MEDLINE, EMBASE and Cochrane Library databases for studies published through May 2018 was performed using the following search algorithm: (a) “choline” or “fluorocholine” or “F-choline” or “C-choline” or “FCH” or “CH” or “FECH” or “FMCH” and (b) “PET” or “positron emission tomography” and (c) “parathyroid” or “hyperparathyroidism”. The diagnostic performance of radiolabelled choline PET was expressed as sensitivity and positive predictive value (PPV) on a per-patient and per-lesion basis and as detection rate (DR) on a per-patient basis, with pooled proportion and 95% confidence interval (95% CI) obtained using a random-effects model. Results Eighteen studies were included in the systematic review. Fourteen articles (517 patients) were selected for the meta-analysis. The meta-analysis provided the following results on a per-patient analysis analysis: sensitivity 95% (95% CI: 92–97%), PPV 97% (95% CI: 95–98%) and DR 91% (95% CI: 87–94%). On a per-lesion analysis, pooled sensitivity and PPV were 92% (95% CI: 88–96) and 92% (95% CI: 89–95%), respectively. No significant heterogeneity was found among the selected studies. Conclusions Radiolabelled choline PET demonstrated excellent diagnostic performance in detecting HP in patients with HPT. Large multicentre studies and cost-effectiveness analyses are needed to better define the role of this imaging method in this setting.